Security issues with remote configuration of internet service providers’ network equipment : specialist thesis = Sigurnosni aspekti udaljenog konfiguriranja mrežne opreme kod pružatelja usluga pristupa internetu : specijalistički rad - Perkov, Luka (L. Perkov ; Fakultet elektrotehnike i računarstva, 2014)
ABSTRACT: CWMP (often called only TR-069) enables internet service provider (ISP) to remotely configure, manage, upgrade and troubleshoot CPE (Customer Premises Equipment). It is a vendor agnostic standard used to manage at least one device per customer. The protocol, used in more then half a billion devices, as well as its security challenges are presented. The security focus is not on a particular implementation but on the protocol flaws in general. Topics include identification problem, transport security and denial of service attacks. The solutions to these issues is presented where possible. -